Preparation and evaluation of duloxetine hydrochloride enteric-coated pellets with different enteric polymers - Chen Kuang; Yinghua Sun; Bing Li; Rui Fan; Jing Zhang; Yumin Yao; Zhonggui He (Elsevier, 2017)
The main purpose of the present study was to prepare duloxetine hydrochloride (DXH) enteric-coated pellets using different enteric polymers. Three layers (drug-loaded layer, barrier layer, and enteric-coated layer) were applied to the inert core pellets, successively. The optimal formulation was manufactured by employing suspension layering method in fluidized bed processor (FBP) with varieties of enteric polymers like Aqoat® AS-LF, Eudragit® L30D55 and HPMCP-HP55. The prepared pellets were measured for physical characterization and the in vitro dissolution profile. Scanning electron microscopy (SEM) was conducted to observe the morphology of pellets, and different kinetic models were applied to analyze the release mechanism of Cymbalta® and home-made pellets. The coating weight gain of enteric-coated layer containing Eudragit® L30D55, Aqoat® AS-LF and HP-55 were determined to be 35%, 26% and 24%, respectively. The similarity factors (f2) of self-made capsules with above polymers and commercially available capsules (Cymbalta®) were above 50 in the dissolution medium of pH 6.8 phosphate buffer solution (PBS). SEM figures showed the smooth surfaces of self-prepared pellets using Eudragit® L30D55 and Aqoat® AS-LF, whereas rough surface was found in the HP-55 pellets at day 0, and an impurity was appearing in the condition of 40 °C/75% relative humidity for 1 month. In conclusion, the pellets prepared by utilizing Eudragit® L30D55 and Aqoat® AS-LF were the optimal preparations based on the dissolution profile and stability.